PENGARUH STRUKTUR MODAL, PROFITABILITAS, LIKUIDITAS DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN DEWAN KOMISARIS SEBAGAI VARIABEL MODERASI - Adiesty Yulia Rahma; Zulfikar Zulfikar (LP2M Universitas Bina Bangsa, 2024)
The purpose of this study is to determine the effect of capital structure, profitability, liquidity, and corporate social responsibility on company value with the board of commissioners as a moderation variable in industrial companies on the Indonesia Stock Exchange for the 2020-2022 period. The population used in this study is industrial companies listed on the IDX in 2020-2022. This study uses multiple linear regression analysis techniques and moderate regression analysis tests using SPSS 26 and in data processing where this technique is used to estimate the value of the dependent variable using more than one independent variable and will be influenced by moderation variables. The result of this study is that capital structure affects the value of companies in industrial companies listed on the Indonesia Stock Exchange for the 2020-2022 period. Profitability affects the value of companies in industrial companies listed on the Indonesia Stock Exchange for the 2020-2022 period. Liquidity affects the value of companies in industrial companies listed on the Indonesia Stock Exchange for the 2020-2022 period. Corporate social responsibility affects the value of companies in industrial companies listed on the Indonesia Stock Exchange for the 2020-2022 period